Polar or Charged Residues Located in Four Highly Conserved Motifs Play a Vital Role in the Function or pH Response of a UPF0118 Family Na+(Li+)/H+ Antiporter - Wang, Lidan; Zou, Qiao; Yan, Mingxue; Wang, Yuting; Guo, Sijia; Zhang, Rui; Song, Yang; Li, Xiaofang; Chen, Huiwen; Shao, Li; Meng, Lin; Jiang, Juquan (Frontiers in Microbiology, 2020)
Functionally uncharacterized UPF0118 family has been re-designated as autoinducer-2 exporter (AI-2E) family since one of its members, Escherichia coli YdgG, was identified to function as an autoinducer-2 exporter. However, it’s very likely that AI-2E family members may exhibit significantly distinct functions due to low identities between them. Recently, we identified one member of this family designated as UPF0118 to represent a novel class of Na+(Li+)/H+ antiporters. In this study, we presented that UPF0118, together with its homologs, should represent an independent group of AI-2E family, designated as Na+/H+ Antiporter Group. Notably, this group shows five highly conserved motifs designated as Motifs A to E, which are not detected in the majority of AI-2E family members. Functional analysis established that polar or charged residues located in Motif A to D play a vital role in Na+(Li+)/H+ antiport activity or pH response of UPF0118. However, three basic residues located in Motif E are not involved in the function of UPF0118, although the truncation of C terminus resulted in the non-expression of this transporter. Therefore, we propose that E179-R182-K215-Q217-D251-R292-R293-E296-K298-S307 located in Motifs A to D can be used for signature functional motifs to recognize whether AI-2E family members function as Na+(Li+)/H+ antiporters. Current findings positively contribute to the knowledge of molecular mechanism of Na+, Li+ transporting and pH response of UPF0118, and the functional prediction of uncharacterized AI-2E family members.